Changing patterns in German education policy making: the impact of international organizations - Dennis Niemann (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2009)
The German sectors of secondary and higher education witnessed far-reaching changes in the last decade. Comprehensive reforms were introduced that essentially altered the educational structure as well as the procedures in policy making. These reforms were massively influenced by international initiatives namely the OECD's PISA study and the Bologna Process accompanied by the EU Commission. Both IOs succeeded in impacting German education reforms by applying various governance instruments that can be described as soft governance. Albeit multiple veto points were present in Germany and traditional German principles of education were contrary to the promoted ideals, the IOs' initiatives resolved these blocking effects of national transformation capacities and had a substantial impact on German education policy making. – – In der letzten Dekade haben weitreichende Reformen den sekundären und tertiären Bildungssektor in Deutschland nachhaltig verändert. Dies gilt sowohl für die Strukturen des Schul- bzw. Hochschulbereichs als auch für den Aspekt der Politikgestaltung im Bildungsbereich. Der zu beobachtende Reformprozess ist maßgeblich von Initiativen auf internationaler Ebene angestoßen und beeinflusst worden - namentlich durch die PISA-Studie der OECD und den Bologna-Prozess, welcher mehr und mehr mit der EU zu assoziieren ist. In beiden Fällen wurde durch die Anwendung vornehmlich weicher Steuerungsmechanismen maßgeblich Einfluss auf die Reformprozesse genommen. Obwohl in Deutschland zahlreiche institutionelle Vetopunkte im Bereich der Bildungspolitik existieren und die traditionellen Prinzipien des deutschen Bildungsverständnisses den von der internationalen Ebene beförderten Idealen teilweise diametral gegenüberstanden, gelang es beiden Internationalen Organisationen bzw. Initiativen diese blockierenden Effekte zu umgehen bzw. zu neutralisieren.
Keywords: 370